2020
DOI: 10.31089/1026-9428-2019-59-9-546-547
|View full text |Cite
|
Sign up to set email alerts
|

The role of adverse occupational factors in the formation of hypertension in workers

Abstract: Studied 147 male workers exposed to a complex of unfavorable production factors (noise, local vibration, fibrogenic aerosols, static and dynamic loads) were evaluated occupational hazards categorical. Among the studied professional factors, the significance of noise in the Genesis of hypertension was established

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent publications tend to concentrate more and more on physical factors (noise and vibration) and their significant role in hypertension occurrence [42,[46][47][48]. Experts revealed that noise made the greatest contribution in arterial hypertension developing in workers exposed to a set of adverse occupational factors (noise, vibration, aerosols, static and dynamic loads).…”
mentioning
confidence: 99%
“…Recent publications tend to concentrate more and more on physical factors (noise and vibration) and their significant role in hypertension occurrence [42,[46][47][48]. Experts revealed that noise made the greatest contribution in arterial hypertension developing in workers exposed to a set of adverse occupational factors (noise, vibration, aerosols, static and dynamic loads).…”
mentioning
confidence: 99%